The role of pentacoordinate Al3+ sites of Pt/Al2O3 catalysts in propane dehydrogenation - Yan Wang; Chunlei Pei; Xianhui Wang; Guodong Sun; Zhi-Jian Zhao; Jinlong Gong (Fundamental Research)
Pentacoordinate Al3+ (Al3+penta) sites on alumina (Al2O3) could anchor and stabilize the active site over the catalyst surface. The paper describes the specific effect of Al3+penta sites on the structure and the catalytic performance of Al2O3 supported Pt catalysts by modulating the quantity of Al3+penta sites. The Al3+penta site content of Al2O3 exhibits a volcano-type profile as a function of calcination temperature due to the structural rearrangement. The loading of Pt and subsequent calcination can consume a significant portion of Al3+penta sites over the Al2O3 support. We further find that, when the calcination temperature of the impregnated Al2O3 is higher than the calcination temperature of Al2O3 precursor, the structural rearrangement of Al3+penta sites could make Pt partially buried in Al2O3. Consequently, this partially buried structure leads to relatively low conversion but high stability for propane dehydrogenation. This work further elucidates the stabilization mechanism of the Al3+penta site over Al2O3 support.